Mapping Student Engagement: Analyzing the Nexus of Course Engagement, Resource Utilization, and Online Tutorial Participation - Tita Rosita; Sendi Ramdhani; Amalia Sapriati (STAI Hubbulwathan Duri, 2023)
The purpose of this study was to analyze the intensity of students in accessing essential and enrichment materials; the relationship between Course Hits, Resource with access, Days with Access, and Tuton; and the Effect of Course Hits, Resource with access, Days with Access, on Tuton. This research is descriptive research and tests the effect using a quantitative approach. The population in this study were all classes of Masters students at one of the open universities Based on research findings, the majority of students do not access essential materials and enrichment materials. Course hits and tutor scores have a weak correlation, even though there is a significant effect on Course Hits scores, the effect is only 5%. Likewise, resources with access and the value of Tuton have a very weak correlation, even though there is a significant effect of Resources with access on the value of Tuton by 9%. Then the correlation of Days with Access with the Tuton Score is 0.411, which is in the sufficient category dan there is a significant effect of Days with access on Tuton score, the effect is 16%. There is a jointly significant effect between course hits, days with access, and resources with access, on the online tutorial score, with an effect of 24%. Students have not made maximum use of the material presented in the study so online tutorial materials must be made that can encourage students to use them.